(untitled) (International Journal of Engineering and Computer Science, 2017)
The Internet of Things (IoT) is becoming one of the milestones in the era of communication and networking which is going to determine future of IT. The explanation goes on to say that “The Internet of Things is such a radical concept that it is a challenge to even imagine all the possible ways in which it will affect business, economies, and society”. Internet-of-Things (IoT) is the junction of Internet with RFID, Sensor and smart objects. IoT can be defined as “things belonging to the Internet” to supply and access all of real-world information. The Internet of Things (IoT) is a pervasive Internet-based network. Although it makes appreciable development, there are still uncertainties about security concepts of its usage that is usually considered as a major concern in the design of IoT architectures. However, the IoT exhibits characteristics that pose considerable risks: inherent openness, heterogeneity, and terminal vulnerability. This paper mainly focusing on survey of analyzing all security issues and suggested countermeasure. And as IoT contains four layers: perception layer, network layer, support layer and application layer, this paper will analyze the security problems of each layer separately. The study defines security requirements and challenges that are common in IoT implementations and discusses security threats and related solutions to make this technology secure and more prevalent accordingly and suggested further areas of research needed.